Dieta de Podocnemis erythrocephala (Testudines: Podocnemididae) no Parque Nacional do Jaú, Amazonas, Brasil. - Santos Junior, Ladislau Brito (Instituto Nacional de Pesquisas da Amazônia - INPA, 2009)
The diet of Podocnemis erythrocephala was studied during the flooding of the Jaú River in the National Park of Jaú, Amazonas, Brazil. Stomach contents of 42 adults (17 males and 25 females) were collected using stomach flushing technique. I analyzed the frequency of occurrence, volume percentage and index of relative importance. The similarity of the diet between males and females was measured using the simplified Morisita index. To asses differences in percent volume of animal matter ingested by males and females the ANOVA test was applied. Plants occurred in all samples and represented 96.79% of the total volume in females and 91.54% of volume in males. The main plant families were Fabaceae, Simaroubaceae, Sapotaceae, Loranthaceae, Lentibulariaceae and Poaceae. Fruits and seeds were the most represented items in the diet of irapucas, present in more than 96% of the samples representing 47.73% of the total volume. Animal matter occurred in 64.68% of males and 76% of females, though the difference in percent volume was not significant. The similarity of the diets of males and females was very high: 0.87. P. erythrocephala is an herbivorous freshwater turtle that feeds mainly on fruits and seeds of the flooded forest. The plant families most representative in the diet were also the most abundant at the Jaú River and the Negro River. There are no apparent differences in the diet of males and females. The detailed information about the diet will be very useful for the conservation and management of this species of freshwater turtle.
Keywords: Quelônios; Irapuca